(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
Preschool education organization is considered the first stage of continuous education system. The pre-school education organization takes a leading position in educating and developing children, preparing them for school. Preschool education organizations are the main part of this system and have important tasks of conducting public education. This article provides details about the structure of preschool education organizations in Uzbekistan and their different types.